Plasticidade fenotípica de Eugenia hiemalis Cambess. (Myrtaceae) em resposta à luz. - Nascimento, Kariny Cari (2015)
The phenotypic plasticity is the ability of a given genotype produce different phenotypes in response to the environment. Plants develop plastic responses to a variety of environmental conditions, both biotic and abiotic, that they are exposed to. Light is a decisive factor for plants, determining largely its survival capacity in the environment. Phenotypic plasticity in response to light is well known, and studies in this area has progressed in recent years. Although this, many gaps remaining to be filled in this fascinating research field, that even old, still motivates scientists around the world. Thus, the aim of this work is study, through observation and experimentation, related aspects of plasticity manifestation in eophylls, collection techniques interference in adult leaves, equivalence of individual and population plasticity, as well the manifestation of plasticity over time in modular and individual characteristics using Eugenia hiemalis Cambess. (Myrtaceae) as a model. E. hiemalis is a specie found in different light environments into the riparian zone belonging to the upper Paraná river floodplain, which suggests the existence of some degree of phenotypic plasticity in response to light. For study proceeding, simulation experiments were conducted in different light conditions with shade cloth, where was held the anatomical analysis eophylls, anatomical studies of adult leaves field collected and plants ecophysiological evaluation. The results show that E. hiemalis presents great phenotypic plasticity, which is manifested in eophylls as well showed different manifestation for adult leaves collection techniques. Evidence of difference between populational and individual phenotypic plasticity were also found, as well plasticity may differentially manifests between individuals and modular features over time. Therefore, even being an old field of study, carry out studies in this direction still have a lot to offer to its development. Thus, future researches that develop the ideas here shown and offer new insights into the phenotypic plasticity in response to light is encouraged.